Natural Solutions for Bacterial Infections: Evaluating the Efficacy of Sedum Album sp Plant Extract against Gram-Positive and Gram-Negative Bacteria - Rezgallah Younis Mahmoud Rezgallah; Garnasah Ahmed Asmeedah; Aml Ahmed Asmeedah; Seham Alsharif Salheen; Afya Atoumi Baroud (المجلة الأفروآسيوية للبحث العلمي, 2024)
With the rise of antibiotic resistance, there is an urgent need for alternative and effective treatments for bacterial infections. Natural compounds derived from plants have gained considerable attention for their potential antimicrobial properties. This study aims to explore the efficacy of Sedum album sp plant extract against both Gram-positive and Gram-negative bacteria, shedding light on its potential as a natural solution for bacterial infections.The study concluded the antimicrobial activity observed in the extract of Sedum album sp indicates the presence of bioactive compounds that hold promise for potential therapeutic applications it also indicated that the application of Sedum album sp plant extract has demonstrated significant potential in combating both Gram-positive and Gram-negative bacteria. The observed antimicrobial activity suggests the presence of bioactive compounds with therapeutic applications. However, further studies are needed to identify and isolate the specific constituents responsible for these effects, as well as to elucidate their mechanisms of action